Hybrid war as a form of modern international conflicts and its influence on accounting development - Zhyhlei, Iryna; Legenchyk, Segiy; Syvak, Olena (Przegląd Wschodnioeuropejski, 2020)
The article is devoted to the study of hybrid warfare, as well as its influence on the reflection of business transactions in the accounting system. The study was conducted using the following research methods: analysis; synthesis; logical method; systematization, comparison, generalization, historical method. As a result, the features inherent in modern hybrid wars, including Ukrainian-Russian, as well as the specifics of accounting that arise during hostilities with emphasis on accounting features in enterprises whose assets were under the direct influence of hostilities, in particular, in the uncontrolled territories of Luhansk and Donetsk regions of Ukraine.